2019
DOI: 10.1158/1055-9965.epi-19-0114
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Human Papillomavirus Types 6 and 11 Genetic Variants and Cervical Abnormalities: The Ludwig–McGill Cohort Study

Abstract: Background: Human papillomavirus (HPV) types 6 and 11 are mainly associated with the development of genital warts and recurrent respiratory papillomatosis. We examined intratypic genetic variability of both viral types with the development of cervical cytologic abnormalities in Brazilian women.Methods: We used PCR sequencing to characterize variants of HPVs 6 and/or 11 in cervical swabs from women in the Ludwig-McGill Cohort Study. We used a binomial generalized estimating equations (GEE) model with logit link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…22 We also evaluated the frequency and clinical correlates of HPVs 6 and 11 variants infection in 79 and 39 women enrolled to the Ludwig/McGill cohort study, 41 respectively, throughout a follow-up period up to 10 years, and observed that cervical cytological abnormalities were not affected by HPV intratypic heterogeneity. 23 It needs to be highlighted that within these women we were unable to characterize the molecular variant in 22.5% of the smears, and that solely 17 and 5…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…22 We also evaluated the frequency and clinical correlates of HPVs 6 and 11 variants infection in 79 and 39 women enrolled to the Ludwig/McGill cohort study, 41 respectively, throughout a follow-up period up to 10 years, and observed that cervical cytological abnormalities were not affected by HPV intratypic heterogeneity. 23 It needs to be highlighted that within these women we were unable to characterize the molecular variant in 22.5% of the smears, and that solely 17 and 5…”
Section: Discussionmentioning
confidence: 96%
“…On contrary, within 89 HPV‐11 positive HIM participants (42 developed GWs) among whom variants from the A2 sublineage were the more frequently detected, no association of specific variants with the clinical disease was observed 22 . We also evaluated the frequency and clinical correlates of HPVs 6 and 11 variants infection in 79 and 39 women enrolled to the Ludwig/McGill cohort study, 41 respectively, throughout a follow‐up period up to 10 years, and observed that cervical cytological abnormalities were not affected by HPV intratypic heterogeneity 23 . It needs to be highlighted that within these women we were unable to characterize the molecular variant in 22.5% of the smears, and that solely 17 and 5 HPVs 6 and 11 positive women developed ASCUS (atypical cells of undetermined significance) or LSIL during the study period, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations